Reconstruction of Islamic Banking Financing Dispute Settlement in Indonesia: A Paradigm Shift from Adversarial to Consensus - Upi Sopiah Ahmad; Muhammad Sya'ban Siregar; Mhd.Syahnan; Akmaluddin Syahputra; Mhd Yadi Harahap (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The settlement of Islamic banking financing disputes in Indonesia is still dominated by the adversarial litigation paradigm, which is oriented towards formal legal certainty and a win-lose solution pattern. This condition indicates that the Islamic economic dispute resolution mechanism still tends to adopt the adjudicative model of modern civil law, thus not fully aligned with the relational character of muamalah transactions that are based on partnership, justice, and the sustainability of economic relations between the parties. This study aims to analyze the weaknesses of the adversarial paradigm in the settlement of Islamic banking financing disputes and reconstruct a consensus-based dispute resolution model through the maqāṣid al-syarī'ah approach. This study is a normative legal study with a statutory, conceptual, and philosophical approach. Legal materials are analyzed normatively and qualitatively using the Maqāṣid-Based Dispute Governance (MBDG) framework. The results show that the dominance of formal litigation causes dispute resolution to be more oriented towards legal proof and fulfillment of contractual obligations rather than restoring economic relations between the parties. This article offers a hybrid dispute resolution model based on the maqāṣid al-syarī'ah (the principles of Islamic law) that integrates negotiation, sulh-based mediation, sharia arbitration, and litigation in stages, placing litigation as the ultimum remedium. The novelty of this article lies in the formulation of MBDG as a conceptual framework that reorients sharia economic dispute resolution from a dispute resolution pattern to dispute governance based on the benefit, substantive justice, and sustainability of the economic relations of the parties